2013
DOI: 10.1111/bju.12008
|View full text |Cite
|
Sign up to set email alerts
|

Ureteroscopic management of upper tract urothelial carcinoma (UTUC) in patients with Lynch Syndrome (hereditary nonpolyposis colorectal cancer syndrome)

Abstract: Objectives To report our experience with ureteroscopic laser ablation of upper tract urothelial carcinoma (UTUC) in patients with Lynch Syndrome (LS), as defined by a documented germline mutation in the MSH‐2 gene. To increase awareness among urologists about UTUC in this unique patient population and refer to genetic counselling when appropriate. Patients and Methods Demographic, clinical and pathological data on 13 consecutive patients with UTUC and documented MSH‐2 mutation comprising 15 involved renal u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 32 publications
0
24
0
Order By: Relevance
“…Therefore, low malignant potential might be characteristic of LS‐associated UUTC, as it is of LS‐associated colorectal cancer. Although we experienced no bilateral UUTCs, a recent retrospective study reported a potentially increased risk of bilaterality . It is important to detect LS‐associated UUTC early and to survey the development of metachronous UUTC on the contralateral side.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Therefore, low malignant potential might be characteristic of LS‐associated UUTC, as it is of LS‐associated colorectal cancer. Although we experienced no bilateral UUTCs, a recent retrospective study reported a potentially increased risk of bilaterality . It is important to detect LS‐associated UUTC early and to survey the development of metachronous UUTC on the contralateral side.…”
Section: Discussionmentioning
confidence: 80%
“…As this limitation makes our conclusions weak, thoughtful interpretation and consideration of our data is required. MLH1/PMS2 protein loss is often caused by the hypermethylation of the MLH1 promoter region in elderly patients with colorectal cancer, which was not known in LS‐associated UUTCs . In one case with dual MLH1/PMS2 protein loss, we could not carry out genetic testing or BRAFV600E mutational status testing to examine hypermethylation of the MLH1 promoter region .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 They also described the effectiveness of ureteroscopic laser ablative treatment in patients with LS who had UTUC. Although selection bias cannot be ruled out, the potential for bilaterality should be considered, therefore, encouraging kidney preservation when clinically feasible.…”
Section: Includedmentioning
confidence: 99%
“…Yamada et al [1] recently reported a similar case of metachronous upper tract TCC associated with hereditary nonpolyposis cancer (HNPCC) requiring radical surgery. Hubosky et al [2] reported that of 13 HNPCC patients treated for upper tract TCC, 6 had bilateral disease.…”
mentioning
confidence: 99%